RETRACTED ARTICLE: Kaempferol promotes proliferation, migration and differentiation of MC3T3-E1 cells via up-regulation of microRNA-101 - Yang Wang; Hongyu Chen; Hanyang Zhang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Yang Wang, Hongyu Chen & Hanyang Zhang (2019) Kaempferol promotes proliferation, migration and differentiation of MC3T3-E1 cells via up-regulation of microRNA-101. Artificial Cells, Nanomedicine, and Biotechnology, 47(1), 1050–1056, DOI: 10.1080/21691401.2019.1591428Since publication, the authors repeated some of their experiments and found that under the same conditions they could not repeat the results reported in this paper. In addition, they lost all of the original data and images used in this paper. As this directly impacts the reported results and conclusions the authors alerted the issue to the Editor and Publisher and all have agreed to retract the article to ensure correction of the scholarly record.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.